A test of the technology acceptance model for understanding the ICT adoption behavior of rural young entrepreneurs - Zaremohzzabieh, Zeinab; Abu Samah, Bahaman; Muhammad, Mahazan; Omar, Siti Zobidah; Bolong, Jusang; Hassan, Md Salleh; Mohamed Shaffril, Hayrol Azril (Canadian Center of Science and Education, 2015)
Information and communication technologies (ICTs) open up new opportunities for rural young entrepreneurs to enhance their businesses. However, the challenges of adopting and using ICTs obstruct these businesses from growing into drivers for rural-economic development and job creation. The purpose of this paper is to seek to validate the technology acceptance model (TAM), which measures the volitional aspect of the ICT adoption behavior of young entrepreneurs in a rural community. In order to test the model, data are collected using self-administered questionnaires from 400 rural youth entrepreneurs. The structural equation modeling technique (SEM) was applied to assess the model. The results confirmed that TAM is robust enough to gauge the dimensions of young entrepreneurs’ adoption of ICT by way of the model accounting for 55 percent of the variance in intention to use ICT. They also indicated that attitude toward entrepreneurship partially mediated the relationship between ICT’s usefulness and entrepreneurial intention. This paper will serve to illuminate this model and reveal new knowledgeperspectives. Policy makers could encourage rural youth entrepreneurs to use ICT in their businesses, which will in turn inspire other entrepreneurs to look up to these adopters and follow them, thus increasing the use of ICT in rural communities.